Aluminum-doped lead-free double perovskite Cs2AgBiCl6 nanocrystals with ultrahigh stability towards white light emitting diodes. (March 2022) - Li, Lifang; Shao, He; Wu, Xiufeng; Chen, Wenda; Zhu, Jinyang; Dong, Biao; Xu, Lin; Xu, Wen; Hu, Junhua; Zhou, Mi; Ji, Yuan; Song, Hongwei; et al.
Highlights: Al 3+ -Cs2 AgBiCl6 NCs are successfully synthesized. Al 3+ -Cs2 AgBiCl6 NCs show bright STE emission with PLQY ∼17.2%. Al 3+ -Cs2 AgBiCl6 NCs exhibit ultrahigh air stability. A WLED based on lead-free perovskite NCs is realized. Abstract: Lead-free halide perovskite nanocrystals (NCs) have caused widespread concerns for solving the toxicity and instability problems of lead perovskites. Here, we synthesized Al 3+ -Cs2 AgBiCl6 . Through controlling the doping content of Al 3+ ions, the Al 3+ -Cs2 AgBiCl6 exhibit bright self-trapped exciton (STE) red emission. The photoluminescence quantum efficiency (PLQY) increases significantly from 0.98% to 17.2%, which is higher than the record value (16%) of the currently reported red-emitting lead-free double perovskite. The enhancement of PL of NCs is accomplished by indirect to direct bandgap transition assisted by doping of Al 3+ ions, as supported by density functional theory (DFT) calculations. Moreover, the Al 3+ -Cs2 AgBiCl6 exhibit ultrahigh stability and can maintain their original structure for more than 7 months, which demonstrates the best stability comparing with the reported double perovskite nanocrystals. Finally, the white light emitting diode (WLED) was fabricated. These results provide opportunities for the future application of lead-free double perovskite in the field of optoelectronics. Graphical abstract: Image, graphical abstract